(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The history of freedom in America is a story of struggle, sacrifice, and progress. From the fight for independence from British rule to the expansion of civil rights and democratic freedoms, the United States has undergone a long journey toward realizing the ideals of liberty and equality. Although freedom was not equally available to all people throughout American history, the nation has continually worked to expand these rights to more citizens.